Low serum free light chain is associated with risk of COPD exacerbation. Issue 2 (6th July 2020) - Tanimura, Kazuya; Sato, Susumu; Sato, Atsuyasu; Tanabe, Naoya; Hasegawa, Koichi; Uemasu, Kiyoshi; Hamakawa, Yoko; Hirai, Toyohiro; Muro, Shigeo
Background: Most exacerbations of chronic obstructive pulmonary disease (COPD) are triggered by respiratory tract infections. Adaptive immunity via antibody production is important in preventing infections. Impaired antibody production is reported to be associated with an increased risk of exacerbations of COPD. In the present study, we elucidated whether reduced free light chains (FLCs), which are excessive amounts of light chains produced during antibody synthesis and can be used to estimate systemic antibody production, may be a promising biomarker to predict the risk of exacerbations of COPD. Methods: We enrolled stable male patients with COPD and prospectively observed them for 2 years. At baseline, serum combined FLC (cFLC; sum of kappa and lambda values) and pulmonary function were evaluated. Exacerbation was defined as a worsening of symptoms requiring treatments with antibiotics, corticosteroids or both. Results: 63 patients with stable COPD were enrolled (72.8±8.1 years, GOLD A/B/C/D=24/28/6/5), and 51 patients completed the 2-year follow-up. Serum cFLC was 31.1 mg·L −1 on average and ranged widely (1.4 to 89.9 mg·L −1 ). The patients with low cFLC (below the mean−sd, n=6) experienced a significantly shorter time to the first exacerbation of COPD (p<0.0001 by the log-rank test). A multivariate Cox proportional hazard model, including the COPD assessment test score, % predicted forced expiratory volume in 1 s (FEV1 % pred), and number of previous exacerbations demonstrated that low cFLC and low FEV1 % pred were independently and significantly correlated with the risk for exacerbations of COPD. Conclusion: Low cFLC may be a B-cell-associated novel biomarker associated with risk of COPD exacerbation. Impaired antibody production is associated with an increased risk for exacerbations of COPD. Low serum free light chain is a novel B-cell-associated biomarker for COPD exacerbations. https://bit.ly/35cgMTC